Interaction of Psychological Factors in Shaping Entrepreneurial Intention among Computer and Electrical Engineering Students - Chao-Tung Liang; Jia-Ling Lee; Chaoyun Liang (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Numerous technopreneurs start their ventures at college age, but the entrepreneurship of computer and electrical engineering (CEE) students remains under-studied. This study analysed both the combined and interactive effects of psychological factors on the entrepreneurial intentions of CEE students. In this study, entrepreneurial intention comprised two dimensions, conviction and preparation. Regarding the direct effects, the results indicated that self-efficacy affected entrepreneurial conviction the most, followed by negative emotion, intrinsic motivation, and metacognition. Negative emotion affected entrepreneurial preparation the most, followed by self-efficacy and positive emotion. The results also revealed several crucial interactive effects resulting from psychological factors. An increase in cognitive load increased the entrepreneurial intention of students exhibiting high intrinsic motivation and reduced the intention of students exhibiting low intrinsic motivation. An increase in metacognition increased the entrepreneurial conviction of students exhibiting either high or low intrinsic motivation. An increase in positive emotion reduced the entrepreneurial intention of students exhibiting high negative emotion and increased the intention of students exhibiting low negative emotion. An increase in self-efficacy increased the entrepreneurial intention of students exhibiting either high or low negative emotion.